Climate Crisis: Adaptive Approaches and Sustainability - Chatterjee, Uday.; Shaw, Rajib; Kumar, Suresh; Raj, Anu David; Das, Sandipan (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book aims to contribute to the discourse on climate crisis by bringing together high-quality empirical research on adaptive approaches and sustainability case studies from across the world. The book is divided into six sections. The introductory section has two chapters which sets the ground of the book as it discusses the framing of climate crisis and the different approaches towards it. It also situates the book within the global discourse. The first chapter seeks the traditional approaches to bridge the gap in the new climate science, while the second chapter delivers the ultimate reasons for temperature change, global warming and its consequences (extreme weather events) in a comprehensive way. It is hoped that the book as a whole will provide a timely synthesis of a rapidly growing and important field of climate science but will also bring forward new and stimulating ideas that will shape a coherent and fruitful vision for future work for the community of Undergraduates, Postgraduates, Ph.D. Scholars and Researchers in the fields of environmental sciences, humanistic and social sciences and geography. In addition, policy and decision makers, environmentalists, NGOs, corporate sectors, social scientists, and government organizations will find this book to be of great value. We believe that a diverse group of academics, scientists, geographers, environmentalists, environmental regulators, social scientists, and sustainable scientists with a common interest within the earth environmental sciences and humanistic and social sciences will find this book to be a comprehensive source for reference. Also, we strongly deemed that it will also provide some support for various levels of organizations and administrations for developing and achieving UN Sustainable Development Goals by 2030 in purview of climate change.
Section I. Introduction -- Chapter 1. Global Warming and Climate Crisis/Extreme Events -- Chapter 2. Ecosystem Degradation to Restoration: A Challenge -- Chapter 3. Exploring the Dynamics of Antarctic Sea Ice over Four Decades Using Geospatial Technology -- Chapter 4. Climate Change and Himalayan Glaciers: A Socio-Environmental Concern in Anthropocene Epoch -- Chapter 5. Indigenous Strategies and Adaptive Approaches to Scrabble Recent Climate Crisis in Two Districts (Bankura and Purulia) of West Bengal, India -- Section II. Climate Crisis Geophysical Hazard and Risk Reduction and Mitigation -- Chapter 6. Addressing Climate Crisis through Coastal Risk Management: What are the Options? -- Chapter 7. Land Degradation and Its Relation to Climate Change and Sustainability -- Chapter 8. Social Resilience of Local Communities due to Tidal Flooding on the North Coast of Semarang City, Indonesia -- Chapter 9. Effects of Climatic Risks on Soil Erosion/Desertification in Southern and Northern Nigeria Using GIS/Remote Sensing Analysis -- Chapter 10. Strategies for Compound Urban and Climate Hazards: Linking Climate Adaptation and Sustainability to Address Risk in Environmental Justice Communities -- Section IIII. Climate Crisis and Smart Agriculture and Food Security -- Chapter 11. The Role of Indigenous Climate Forecasting Systems in Building Farmers' Resilience in Nkayi District, Zimbabwe -- Chapter 12. Agroforestry Practices: A Sustainable Way to Combat the Climate Crisis and Increase Productivity -- Chapter 13. Climate Crisis and Adoption of Climate-Smart Agriculture Technologies -- Chapter 14. Farming Technologies and Carbon Sequestration Alternatives to Combat Climate Change through Mitigation of Greenhouse Gas Emissions -- Chapter 15. Nature-based Solutions (NbS) for Dryland Agriculture in Semi-Arid Regions of Maharashtra, India: A Short Review with Possible Approaches for Building Climate Resilience -- Chapter 16. Smart Farming and Carbon Sequestration to Combat the Climate Crisis -- Chapter 17. Alleviation of the Climate Catastrophe in Agriculture through Adoption of Climate-Smart Technologies -- Chapter 18. Climate Crisis and Adoption of Climate-Smart Agriculture Technologies and Models -- Section IV. Climate Crisis and Urban Health -- Chapter 19. Mainstreaming Biodiversity in Urban Habitats for Enhancing Ecosystem Services: A Conceptual Framework -- Chapter 20. Climate-Resilient Agropolitan Approach towards Sustainable Regional Development of Barddhaman District of West Bengal -- Chapter 21. Analysing Sustainable Approaches in MGNREGA Works for Climate Change Adaptation: A Case Study of Debra Block, West Bengal, India -- Chapter 22. Urban Heat: UHI and Heat Stress Threat to Megacities -- Chapter 23. Assessment of LULC Changes and its Impact on Surface Temperature and Urban Heat Island Conditions in Kolkata during SARS COVID-19 period -- Chapter 24. Addressing Climate Changes Challenges in South Africa: A Study in KwaZulu Natal Province -- Section V. Climate Crisis and Land Water and Forest Sustainability -- Chapter 25. Evaluating the Potential Impact of Climate Change on Glacier Dynamics in Western Himalayas, India -- Chapter 26. The Tale of Crab Collectors and Fatteners: Negotiating Climate Change in Indian Sundarbans -- Chapter 27. Climate Crisis and Wetland Ecosystem Sustainability -- Chapter 28. Land Suitability Assessment for Mulberry-based Agroforestry Using AHP and GIS Technique in North-Western Himalayan Region of Kashmir Valley, India to Achieve Sustainable Agriculture -- Chapter 29. Climate Crisis and Coastal Risk Management.
Keywords: Climatology; Sustainability; Climate Sciences; Sustainability